2020
DOI: 10.1111/jch.14151
|View full text |Cite
|
Sign up to set email alerts
|

Validation of novel identification algorithms for major adverse cardiovascular events in a Japanese claims database

Abstract: Major adverse cardiovascular events (MACEs), such as stroke and myocardial infarction (MI), are the most common cause of death worldwide (the second leading cause in Japan), and their prevention is critical in healthcare. 1-3 Hypertension, hyperlipidemia, and diabetes mellitus are known risk factors for MACEs, and a number of pharmaceutical agents have been developed to control the risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…[2][3][4][5][6][7][8] Secondary outcome Secondary outcome variables were classi ed postoperatively as follows: cardiovascular complications: composed of Acute myocardial infarction (STEMIs & NSTEMIs), new congestive heart failure, non-fatal cardiac arrest and death within 7 days postoperatively. [9][10][11][12]…”
Section: Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] Secondary outcome Secondary outcome variables were classi ed postoperatively as follows: cardiovascular complications: composed of Acute myocardial infarction (STEMIs & NSTEMIs), new congestive heart failure, non-fatal cardiac arrest and death within 7 days postoperatively. [9][10][11][12]…”
Section: Primary Outcomementioning
confidence: 99%
“…Acute kidney injury (AKI) commonly occurs in patients after noncardiac surgery and in 17.9% of patients following major surgery. [1][2][3][4][5][6][7][8][9] The mortality rate of patients experiencing AKI increases signi cantly. [3][4][5] Many risk factors such as body mass index (BMI), gender, age, African American race, preexisting hypertension, active congestive heart failure, chronic kidney disease, pulmonary disease, insulin-dependent diabetes mellitus, peripheral vascular disease, presence of ascites and complexity of the surgery advanced age cannot be modi ed.…”
Section: Introductionmentioning
confidence: 99%
“…18 MACEs have been extensively used as a cardiovascular outcome after particular medical management or after undergoing certain procedures. 19 Also, recent evidence has shown that periodontal disease inflammation is an independent predictor of the risk of MACEs, sug-gesting that arterial inflammation is the link behind this association. 20 Our study hypothesis (alternative) is that, given the smaller size of the penile vessels, the diagnosis of ED and periodontitis can be predictive and additive factors for future MACEs.…”
Section: Introductionmentioning
confidence: 99%
“…The definition varies between studies, referring to a bigger composite endpoint, including heart failure, acute coronary syndrome (stable and unstable), coronary artery bypass grafting, or percutaneous coronary intervention 18 . MACEs have been extensively used as a cardiovascular outcome after particular medical management or after undergoing certain procedures 19 . Also, recent evidence has shown that periodontal disease inflammation is an independent predictor of the risk of MACEs, suggesting that arterial inflammation is the link behind this association 20 …”
Section: Introductionmentioning
confidence: 99%
“…For codes with low accuracy, researchers should make study inclusion decisions based on the combination of the diagnostic codes and clinical evidence, such as related treatments for stroke. Shima et al 15 also reported that the positive predictive values (PPVs) for outcome identification algorithms were increased when event-specific treatment data for ischemic stroke were added to the algorithm based on diagnostic codes alone. However, there is few evidence regarding the validity of identification algorithms consisting of ICD-10 diagnostic codes in combination with other measures for hospitalized patients with AIS 16,17 in administrative databases, such as diagnostic imaging, drug administration, mechanical thrombectomy, or rehabilitation.…”
Section: Introductionmentioning
confidence: 99%